1998
DOI: 10.1111/j.1532-5415.1998.tb06644.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pain in Cognitively Impaired Compared with Cognitively Intact Older Patients with Hip‐Fracture

Abstract: Pain is treated poorly in older postoperative patients. Cognitive impairment and age strongly influence the amount of analgesic nurses administer to older patients after surgical repair of hip fracture. Provision for patient comfort is a fundamental ethical obligation of healthcare providers. Clinicians need to pursue this goal more aggressively, especially for cognitively impaired, postoperative older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
166
6
14

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 277 publications
(199 citation statements)
references
References 30 publications
10
166
6
14
Order By: Relevance
“…48,51 Advanced age is the strongest predictor of receiving no analgesic for painful conditions in EDs. 52 Older adults are less likely to receive pain medication than younger adults with similar conditions involving cancer, 53 trauma, 54 hip fracture, [55][56][57] and orthopedic injuries. 58 Indeed, among older ED patients with isolated long-bone or hip fractures, more than one-third receive no analgesia in the ED, 52,56,59 and only 57% receive opioid medication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…48,51 Advanced age is the strongest predictor of receiving no analgesic for painful conditions in EDs. 52 Older adults are less likely to receive pain medication than younger adults with similar conditions involving cancer, 53 trauma, 54 hip fracture, [55][56][57] and orthopedic injuries. 58 Indeed, among older ED patients with isolated long-bone or hip fractures, more than one-third receive no analgesia in the ED, 52,56,59 and only 57% receive opioid medication.…”
Section: Resultsmentioning
confidence: 99%
“…Older ED patients are less likely to receive pain medication than younger adults with similar conditions. [53][54][55][56][57][58] More than one-third of older patients with conditions such as isolated long-bone or hip fractures receive no pain medication during ED visits. 52,56,59 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies evaluating the use of observational approaches note that behavioral indicators are more evident when the older person is engaged in activity, such as transfers, ambulation, and repositioning and that observation at rest can be misleading. [11] [34] [35] [ 99] It still remains to be shown whether behavioral observations (e.g., agitation, restlessness, groaning, facial expressions) are sensitive and specific for pain assessment among older persons with dementia. [2] In noncommunicative older adults with severe cognitive impairment, typical pain behaviors may be absent or difficult to interpret because of many confounding factors that can impact behavior in the patient with dementia.…”
Section: Observational Methodsmentioning
confidence: 99%
“…[86] The PPI demonstrates good validity and is feasible for older patients, including those with mild to moderate cognitive impairment, with completion rates up to 65% [39] [99] [121] [127]; however, some researchers note more difficulty with its use by cognitively impaired persons when compared with a descriptor scale with simpler vocabulary. [35] The pain thermometer (PT) [58] [101] is a variation of the VDS in that it is a vertical adjectival scale, but it also illustrates a thermometer along the continuum of adjectives describing pain. The PT is preferred for patients with moderate to severe cognitive deficits or for patients who have difficulty with abstract thinking and communicating verbally.…”
Section: Verbal Descriptor Scalementioning
confidence: 99%
“…In some practice settings, the experiences of older and younger people have been compared to examine pain and analgesic administration and all of the research found no difference in pain intensity between the groups. However, analgesic consumption has been significantly lower in older age groups (Oberle et al 1990, Feldt et al 1998, Celia 2000, Gagliese et al 2000, Gagliese & Katz 2003. Health care professionals administering more analgesics to younger people, older people under-reporting pain and increased sensitivity to opioid analgesia in older people have all been offered as explanations.…”
mentioning
confidence: 99%